Disseminated tuberculosis masquerading as a psychiatric illness—A case report - Shalini Bhaskar; Mimi N. M. Noh (Journal of Family Medicine and Primary Care)
Tuberculosis (TB) can affect any organ, and at times more than one organ in any sequence, in which case it is referred to as disseminated tuberculosis (DTB). We report a patient who presented primarily for psychiatric symptoms of three months’ duration, which later turned out to be a case of DTB involving the central nervous system as well as the spine and lungs. Case Presentation: An elderly lady with subacute onset and worsening behavioural changes of three months’ duration was referred for exclusion of organic brain disease. The neurological and respiratory examination, chest X-ray, electroencephalogram (EEG), and MRI of the brain were normal. She, however, had elevated C-reactive protein, ESR, and raised CSF opening pressure on lumbar puncture. The CSF cell counts, biochemistry, and cultures were within normal limits. Unable to detect a neurological cause for her illness, she was advised to consult a psychiatrist. Two months later she reported to us again, this time essentially for back pain. Investigations for the back pain (including CT spine) revealed a T12 compression fracture with irregularity of the left T12 pedicle and a para-spinal fluid collection. Pus drained from the collection showed mycobacterium tuberculosis bacteria on staining with ZN stain. The CT scan thorax also showed left lower lobe consolidation and a pleural effusion. Contrast CT scan brain revealed subtle meningeal enhancement at the right parietal region. With standard treatment with a four-drug anti-TB regimen (along with a short course of dexamethasone), she improved well. This case report indicates that the initial clinical presentation of TB in general, as well as DTB, can be misleading, resulting in delay in diagnosis and in initiating treatment.